Design and characterization of an eight‐element passively fed meander‐dipole array with improved specific absorption rate efficiency for 7 T body imaging. (27th May 2019) - Zivkovic, Irena; de Castro, Catalina Arteaga; Webb, Andrew
Abstract : Objective: To evaluate the transmit efficiency and specific absorption rate (SAR) efficiency of a new eight‐element passively fed meander‐dipole antenna array designed for body MRI at 7 T, and to compare these values with a conventional directly fed meander‐dipole array. Methods: The main radiating element of the passively fed dipole is printed on one side of a dielectric substrate and is capacitively coupled to a shorter feeding element (connected to the coaxial cable) printed on the opposite side of the substrate. The transmit (B1 + ) field and SAR were simulated on a phantom and on a human voxel model for both a passively fed and a directly fed single element. Two eight‐channel arrays containing, respectively, directly and passively fed meander dipoles were then simulated, and experimental B1 + maps and T2 ‐weighted spin echo images of the prostate were obtained in vivo for four healthy volunteers. Results: In simulations, the mean transmit efficiency (B1 + per square root input power) value in the prostate was ~ 12.5% lower, and the maximum 10 g average SAR was 44% lower for the array containing passively fed dipoles, resulting in ~ 15% higher SAR efficiency for the passively fed array. In vivo RF‐shimmed turbo spin echo images were acquired from both arrays, and showed image SNRs within 5% of one another. Conclusion: A passive‐feeding network for meander‐dipole antennas has been shown to be a simple method to increase the SAR efficiency of a multi‐element array used for body imaging at high fields. We hypothesize that the main reason for the increase in SAR efficiency is the storage of the strong conservative electric field in the dielectric between the feeding element and the radiating element of the dipole. The passive‐feeding approach can be generalized to other dipole geometries and configurations. Abstract : The aim of this work was to evaluate the transmit efficiency and specific absorption rate (SAR) efficiency of a new eight‐element passively fed meander‐dipole antenna array designed for body MRI at 7 T, and to compare these values with a conventional directly fed meander‐dipole array. Results showed approximately 15% higher SAR efficiency for the passive‐feeding network. This approach is a relatively simple method that can be applied to any dipole configuration for high field body MRI.